2014
DOI: 10.1016/j.ssc.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen in materials properties of yttrium trihydride

Abstract: Numerous experiments have shown that the oxygen-free films of YH 3 possess the face-centered cubic ( f cc) structure only at high pressures whereas oxygen-containing YH 3 films crystallize into the f cc lattice at ambient conditions. In this report, by means of first-principles simulations, we provide a detail understanding of the role of oxygen in stabilization of the f cc YH 3 under normal pressure. We performed the oxygen position preferences screening within the f cc unit cell along with geometrical optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…However, theoretical studies have demonstrated that a wide-band gap fcc phase, i.e. transparent-semiconducting, can be achieved at ambient conditions from the oxygenation of YH 3 or YH 2 films [20]. Since yttrium hydride films deposited by sputtering and exposed to air are known to 500 nm 500 nm YH YH oxidize heavily (see discussion below), the diffractogram measured for the YH x films cannot be unambiguously attributed to an YH 3 or YH 2 stoichiometry.…”
mentioning
confidence: 99%
“…However, theoretical studies have demonstrated that a wide-band gap fcc phase, i.e. transparent-semiconducting, can be achieved at ambient conditions from the oxygenation of YH 3 or YH 2 films [20]. Since yttrium hydride films deposited by sputtering and exposed to air are known to 500 nm 500 nm YH YH oxidize heavily (see discussion below), the diffractogram measured for the YH x films cannot be unambiguously attributed to an YH 3 or YH 2 stoichiometry.…”
mentioning
confidence: 99%
“…YHO films contain two types of competing anions, oxygen and hydrogen, both connected to yttrium atoms . By performing the deposition at different H 2 /Ar flow rates and then oxidizing the films, it is possible to obtain YHO thin films with different concentrations of anion vacancies as well as of hydrogen and oxygen anions with [H] and [O] concentrations anti‐correlated with each other.…”
Section: Resultsmentioning
confidence: 99%
“…In the oxidation of yttrium hydrides, because of a stronger affinity of elemental yttrium for oxygen and its preference to exhibit 3+ oxidation state, there appears the concurrency between the incorporated oxygen and host hydrogen for connectivity with the metal center. Since the metal prefers to bind the oxygen atom, the oxidization process of the hydride system is accompanied by two factors: (i) the change of initial valence electron configurations proceeding in terms of delocalization-localization conversion and (ii) a chain of structural transformations leading to a stable condensed phase [72]. One can, therefore, suggest that, when His topochemically replaced by oxygen, the interplay of processes, such as the Y−H covalent bond cleavage and the Y−O ionic bond formation, may keep a certain part of the interstitial hydrogen species in the lattice.…”
Section: Crystal Assembly In Terms Of Structural Transformationsmentioning
confidence: 99%